Effects of El Niño drought on seedling dynamics in a seasonally dry tropical forest in Northern Thailand. Issue 2 (23rd October 2022) - Nutiprapun, Prapawadee; Hermhuk, Sutheera; Nanami, Satoshi; Itoh, Akira; Kanzaki, Mamoru; Marod, Dokrak
Abstract: As El Niño is predicted to become stronger and more frequent in the future, it is crucial to understand how El Niño‐induced droughts will affect tropical forests. Although many studies have focused on tropical rainforests, there is a paucity of studies on seasonally dry tropical forests (SDTFs), particularly in Asia, and few studies have focused on seedling dynamics, which are expected to be strongly affected by drought. Seedlings in SDTFs are generally more drought‐tolerant than those in the rainforests, and the effects of El Niño‐induced droughts may differ between SDTF and tropical rainforests. In this study, we explored the impact of El Niño‐induced drought at an SDTF in northern Thailand by monitoring the seedling dynamics at monthly intervals for 7 years, including a period of strong El Niño. The effects were compared between two forest types in an SDTF: a deciduous dipterocarp forest (DDF), dominated by deciduous species, and an adjacent lower montane forest (LMF) with more evergreen species. El Niño‐induced drought increased seedling mortality in both the forest types. The effect of drought was stronger in evergreen than in the deciduous species, resulting in higher mortality in the LMF during El Niño. However, El Niño increased seedling recruitment only in the DDF, mainly because of the massive recruitment of the deciduous oak, Quercus brandisiana (Fagaceae), which compensated for the mortality of seedlings in the DDF. As a result, El Niño increased seedling density in the DDF and decreased it in the LMF. This is the first long‐term study to identify the differences in the impacts of El Niño on seedlings between the two forest types, and two leaf habits, evergreen and deciduous, in Southeast Asia. Our findings suggest that future climate change may alter the species composition and spatial distribution of seedlings in Asian SDTFs. Abstract : Long‐term monitoring of seedlings in a seasonally dry tropical forest in northern Thailand revealed that the impact of El Niño‐induced drought on seedling dynamics differed between deciduous and evergreen forests. Drought increased mortality in evergreen forests while promoting recruitment only in deciduous forests. As a consequence of the drought, seedling density increased in deciduous forests while decreasing in evergreen forests. Our findings suggest that future climate change may alter the species composition and spatial distribution of seedlings in Asian dry forests, potentially affecting mature trees in the long run.